Drugs and the future : brain science, addiction and society - Nutt, David J., 1951- (Elsevier/Academic Press, 2007)
This book presents 13 reviews collected to present the new advances in all areas of addiction research, including knowledge gained from mapping the human genome, the improved understanding of brain pathways and functions that are stimulated by addictive drugs, experimental and clinical psychology approaches to addiction and treatment, as well as both ethical considerations and social policy. The book also includes chapters on the history of addictive substances and some personal narratives of addiction. Introduced by Sir David King, Science Advisory to the UK Government and head of the Office.